COMPARATIVE ANALYSIS OF PERSONAL FACTORS AFFECTING STRESS OF STUDENTS AT THE FACULTY OF HUMANITIES AND SOCIAL SCIENCES, PHRANAKHON RAJABHAT UNIVERSITY IN BANGKOK - Weerapalangkoon, Weeraphon; Nopporn, Nopporn; Sawasdee, Aksorn (Academic Journal Phranakhon Rajabhat University, 2022)
The objectives of this research were to: 1) study level of factors affecting stress among students of Faculty of Humanities and Social Sciences, Phranakhon Rajabhat University and 2) compare factors affecting stress among students of Faculty of Humanities and Social Sciences Phranakhon Rajabhat University, classified by personal characteristics. The total population was 2,950 students. The sample group of 353 students was selected by using Yamane's computational formula and systematic random sampling. A questionnaire was used for data collection tool. The statistics used for data analysis were frequency, percentage, mean, standard deviation, and t-test to compare the difference between the independent variables with 2 groups using social science software package. The results showed that the level of factors affecting stress among students was overall at a low level (xˉ = 2.58). When considering each aspect, all aspects were also found at a low level. The highest average was the environmental spect (xˉ =2.68), followed by psychological (xˉ =2.56), and social (xˉ =2.52), respectively. The hypothesis testing results showed that students with different genders had no effect on stress with the probability (p) of .01 while students with different ages, different types of accommodation, different parents' marital status, different average monthly income, different smoking and drinking alcoholic beverage didn’t affect student stress with the probability (p) of .100, .718, .096, .081, .307 .167, .416, respectively at the statistical significance level of .05. For students with different year of study, different major, and different chronic diseases affected student stress with the probability of .032, .000, .017 respectively at the statistical significance level of .05.